Endoplasmic Reticulum Stress, Unfolded Protein Response, and Cancer Cell Fate - Corazzari, Marco; Gagliardi, Mara; Fimia, Gian Maria; Piacentini, Mauro (Frontiers in Oncology, 2017)
Perturbation of endoplasmic reticulum (ER) homeostasis results in a stress condition termed ‘ER stress’ determining the activation of a finely regulated program defined as Unfolded Protein Response (UPR) and whose primary aim is to restore this organelle’s physiological activity. Several physiological and pathological stimuli deregulate normal ER activity causing UPR activation, such as hypoxia, glucose shortage, genome instability and cytotoxic compounds administration. Some of these stimuli are frequently observed during uncontrolled proliferation of transformed cells, resulting in tumour core formation and stage progression. Therefore, it is not surprising that ER stress is usually induced during solid tumour development and stage progression, becoming an hallmark of such malignancies. Several UPR components are in fact deregulated in different tumour types and accumulating data indicate their active involvement in tumour development/progression. However, although the UPR program is primarily a pro-survival process, sustained and/or prolonged stress may result in cell death induction. Therefore, understanding the mechanism(s) regulating the cell survival/death decision under ER stress condition may be crucial in order to specifically target tumour cells and possibly circumvent or overcome tumour resistance to therapies. In this review, we discuss the role played by the UPR program in tumor initiation, progression and resistance to therapy, highlighting the recent advances that have improved our understanding of the molecular mechanisms that regulate the survival/death switch.